TaHSP18.6 and TaSRT1 interact to confer resistance to Fusarium crown rot by regulating the auxin content in common wheat - Ning Zhang; Lu Liu; Songgang Li; Yuhui Wei; Wanting Ren; Mengyao Li; Simin Zhao; Zhipeng Sun; Xia Yang; Yan Ren; Mei Yang; Guangming He; et al. (Proceedings of the National Academy of Sciences, 2025)
Fusarium crown rot (FCR) is one of the most serious soil-borne diseases in common wheat and has caused major wheat yield losses worldwide. Here, we identified an 18.6 kDa heat shock protein gene ( TaHSP18.6 ) through combining a transcriptome analysis and a genome-wide association study. We verified the positive role of TaHSP18.6 in regulating wheat FCR resistance using ethyl methanesulfonate (EMS) mutants and genetic transformation. Next, we screened a lysine deacetylase sirtuin-like (TaSRT1) to determine its potential interaction with TaHSP18.6. We demonstrated that TaSRT1 deacetylated TaHSP18.6 and thereby inhibited TaHSP18.6 protein accumulation. Haplotype analysis revealed that the K171M substitution of TaHSP18.6 generated a susceptible haplotype TaHSP18.6 M171 in wheat, and mass spectrometry results implied that K171 is a key lysine acetylation site. We confirmed the differential acetylation level between TaHSP18.6 K171 and TaHSP18.6 M171 by TaSRT1. Analysis of overexpression lines and EMS mutants showed that TaSRT1 negatively regulated wheat FCR resistance. Meanwhile, we identified that TaHSP18.6 interacted with an auxin-responsive protein IAA1 (TaIAA1) that negatively regulated FCR resistance. TaHSP18.6 overexpression and TaSRT1 mutation significantly increased the auxin content. Exogenous application of auxin substantially enhanced wheat FCR resistance. Taken together, we proposed a TaSRT1–TaHSP18.6 model regulating FCR resistance possibly through mediating TaIAA1 to change the endogenous auxin content in wheat plants.